Phosphoproteome analysis reveals a critical role for hedgehog signalling in osteoblast morphological transitions - Marumoto, Ariane [UNESP]; Milani, Renato; da Silva, Rodrigo A. [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; Granjeiro, José Mauro; Ferreira, Carmen V.; Peppelenbosch, Maikel P.; Zambuzzi, Willian F. [UNESP] (Elsevier, 2017)
The reciprocal and adaptive interactions between cells and substrates governing morphological transitions in the osteoblast compartment remain largely obscure. Here we show that osteoblast cultured in basement membrane matrix (Matrigel™) exhibits significant morphological changes after ten days of culture, and we decided to exploit this situation to investigate the molecular mechanisms responsible for guiding osteoblast morphological transitions. As almost all aspects of cellular physiology are under control of kinases, we generated more or less comprehensive cellular kinome profiles employing PepChip peptide arrays that contain over 1000 consensus substrates of kinase peptide. The results obtained were used to construct interactomes, and these revealed an important role for FoxO in mediating morphological changes of osteoblast, which was validated by Western blot technology when FoxO was significantly up-expressed in response to Matrigel™. As FoxO is a critical protein in canonical hedgehog signalling, we decided to explore the possible involvement of hedgehog signalling during osteoblast morphological changes. It appeared that osteoblast culture in Matrigel™ stimulates release of a substantial amounts Shh while concomitantly inducing upregulation of the expression of the bona fide hedgehog target genes Gli-1 and Patched. Functional confirmation of the relevance of these results for osteoblast morphological transitions came from experiments in which Shh hedgehog signalling was inhibited using the well-established pathway inhibitor cyclopamine (Cyc). In the presence of Cyc, culture of osteoblasts in Matrigel™ is not capable of inducing morphological changes but appears to provoke a proliferative response as evident from the upregulation of Cyclin D3 and cdk4. The most straightforward interpretation of our results is that hedgehog signalling is both necessary and sufficient for membrane matrix-based morphological transitions.
Keywords: Bioengineering; Biomaterials; ECM; Osteoblast; Sonic Hedgehog